2011
DOI: 10.2174/138920111794480589
|View full text |Cite
|
Sign up to set email alerts
|

Alpha7 Neuronal Nicotinic Receptors as Targets for Novel Therapies to Treat Multiple Domains of Schizophrenia

Abstract: A number of hypotheses have been put forth to explain the underlying abnormalities of schizophrenia. The widely held dopamine hypothesis suggests that positive symptoms are related to elevated subcortical dopamine transmission and that negative symptoms and cognitive impairments are associated with decreased cortical dopamine function. However, recent evidence suggests broader involvement of serotonergic, glutamatergic and other neurotransmitter systems and a growing body of evidence supports a role for nicoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 131 publications
1
10
0
Order By: Relevance
“…In this context, nicotinic cholinergic receptors have emerged as priority targets and particularly the alpha7 and alpha4 beta2 NNRs (Freedman et al, 2008;Kucinski et al, 2011;Olincy et al, 2007;Ripoll et al, 2004). Although studies of the latter have yielded mixed results , studies of the former, using DMX-B and EVP6124, have shown therapeutic potential in subjects with schizophrenia (EnVivo_Pharmaceuticals, 2009, 2011Freedman et al, 2008;Olincy et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, nicotinic cholinergic receptors have emerged as priority targets and particularly the alpha7 and alpha4 beta2 NNRs (Freedman et al, 2008;Kucinski et al, 2011;Olincy et al, 2007;Ripoll et al, 2004). Although studies of the latter have yielded mixed results , studies of the former, using DMX-B and EVP6124, have shown therapeutic potential in subjects with schizophrenia (EnVivo_Pharmaceuticals, 2009, 2011Freedman et al, 2008;Olincy et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In the wake of the MATRICS initiative, molecular targets for the treatment of CDS have been proposed (Gray and Roth, 2007;Marder et al, 2004). Among the prioritized targets was the alpha7 neuronal nicotinic receptor (NNR; Freedman et al, 2008;Kucinski et al, 2011;Olincy and Stevens, 2007). Initially, preclinical studies indicated that antagonists of this receptor could induce sensory gating deficits in rodents that were similar to those observed in schizophrenia (Luntz-Leybman et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…NMDA receptor dysfunction and dysregulation have been proposed as the final common pathway of positive, cognitive, and negative symptoms in schizophrenia [152]. Use of the positive allosteric modulator of α7nAChR to target positive, cognitive, and negative symptoms in schizophrenia is well documented [153-157]. Therefore, the galantamine-memantine combination has the potential to treat positive, cognitive, and negative symptoms of schizophrenia as shown in Table 2.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…Observed in animal models of SZ and in SZ patients, transient improvements in sensory, attentional, mnemonic and executive functions with acute nicotine/nAChR agonist treatment (D'Souza and Markou 2012; Kucinski et al 2011;Leiser et al 2009;Olincy and Freedman 2012;Radek et al 2010) have collectively promoted the hypothesis of smoking in SZ as self-medication for cognitive deficits mediated via nAChR pathophysiology (Kumari and Postma 2005;Wing et al 2012;Winterer 2010).…”
Section: Introductionmentioning
confidence: 99%